IN TRUST A HISTORY of PNB - White, Nicholas J. (MPH Group Publishing Sdn Bhd, 2018)
"This is the first full-length study of Permodalan Nasional Berhad (PNB; Malaysia's National Equity Corporation), marking the institution's 40th anniversary. A government-linked corporation, PNB is a unique 'hybrid' being both investment company and fund manager. The Corporation was formed with a specific mandate to raise income and savings levels through spreading corporate ownership more evenly throughout the Malaysian economy, particularly amongst the lower income indigenous Bumiputera communities. PNB runs what is reckoned to be the world's largest unit trust scheme, and manages investments which make up at least 10 per cent of Kuala Lumpur's Stock Exchange. This book charts PNB's fascinating history through its origins in the New Economic Policy; the growth and management of its vast investment portfolio; the evolution of its highly successful unit trust schemes encompassing millions of small-scale investors; the international reach of the Corporation's operations; and, PNB's contribution to the development of Malaysian Human Resources (as well as the role played by its own employees in forging this dynamic organisation). In so doing, the book explores global issues of decolonisation and nation-building in a multi-racial society; post-colonial economic development; corporate social responsibility; and, state-led capitalism. The study will appeal to a wide audience within and beyond Malaysia as an alternative model of economic development that could be emulated in other parts of the world"--back cover